Etude de la rémanence d’un savon additionné à l’huile essentielle de citron (citrus limon) - Hassi, Ahlem (My University, 2017)
This work has focused on the valorization of lemon essential oil (Citrus limon). The latter was extracted by steam distillation. The extraction yield obtained is 0.43% with a density of 0.852 which complies with the international standards of essential oils. The test of synthesis of a soap added to the essential oil of Citrus limon was tested, to study its effectiveness and its remanence. The physicochemical characteristics of the soap obtained; pH of 9.65 and caustic free alkali of 0.28%, allowed us to classify the soap in the 2nd range of household soaps. This work has shown that the soap obtained seems to have excellent remanence and the skin of Hands seems protected from bacterial contamination. With a reduction rate of 94.64%; 4 hours after disinfection. The results obtained open up numerous perspectives for studies which could be carried out to compare the effectiveness and the persistence of the soap obtained with other soaps, as witnesses.
Keywords: huile essentielle; Citrus limon; savon; taux de réduction; rémanence.; essential oil; Citrus silt; soap; reduction rate; remanence